2015
DOI: 10.1259/dmfr.20140229
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of different foreign bodies in the maxillofacial region using plain radiography, CT, MRI and ultrasonography: anin vitrostudy

Abstract: In cases with suspected foreign bodies in the maxillofacial region, CT seems to be the optimal initial imaging study. Wood, however, could only be detected using ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
94
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 40 publications
4
94
0
4
Order By: Relevance
“…In 25% of patients there was no specific pulmonary disease. These results were in conformity with previous reports depicting that in patients who were exposed to long-term smoke of organic fuels could develop a wide range of pulmonary problems such as constrictive disease, interstitial lung disease, cancer, asthma and recurrent infections of the lower respiratory tract [10][11][12][13][14]. In a meta-analysis by Hu et al it has been also shown that long-term exposure to the smoke of organic materials may increase the risk of constrictive-obstructive disease significantly [15].…”
Section: Discussionsupporting
confidence: 92%
“…In 25% of patients there was no specific pulmonary disease. These results were in conformity with previous reports depicting that in patients who were exposed to long-term smoke of organic fuels could develop a wide range of pulmonary problems such as constrictive disease, interstitial lung disease, cancer, asthma and recurrent infections of the lower respiratory tract [10][11][12][13][14]. In a meta-analysis by Hu et al it has been also shown that long-term exposure to the smoke of organic materials may increase the risk of constrictive-obstructive disease significantly [15].…”
Section: Discussionsupporting
confidence: 92%
“…10,36 Ultrasonography is also inaccurate in delineating fractures and differentiating soft tissues of the contents of a traumatized globe; it is operator dependent and contraindicated when a ruptured globe is suspected. 15,26,[37][38][39] Another rather novel imaging modality that has been suggested in cases with orbital fractures is CBCT. The major advantage of this modality over conventional CT is the reduced X-ray exposure to the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Javadrashid et al [11] compared the usefulness of 4 imaging modalities in visualizing various foreign bodies of different sizes. In this study, all foreign bodies except wood were visualized best using CT. Wood could only be detected using US, and, then, only when fragments were greater than 0.5 mm in size.…”
Section: To the Editormentioning
confidence: 99%
“…Plain radiography and CT were almost ☆ Author (s) declare that they have no conflict of interest. equally accurate in visualizing metal and graphite, and magnetic resonance imaging was the least useful imaging technique [11].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation